PENGARUH DUKUNGAN SUAMI TERHADAP TINGKAT KECEMASAN IBU SELAMA MASA KEHAMILAN DI BPS SITI AZIZAH WIJAYA, SST SUKOLILO BARAT BANGKALAN - Heriyanto, Bambang (WAHANA, 2014)
Support and role husband during pregnancy improve the readiness pregnant mother in face and pregnancy. But practically do not all husband give support its wife during pregnancy. This research aim to study Influence husband support to anxiety mother during a period pregnancy in BPS Siti Azizah Wijaya, SST Sukolilo Barat Bangkalan.Research method is analytic, population all pregnant mother, sampel counted 20 people by simple sampling random. Independent variable is husband support, variable dependen mount anxiety. Method data collecting use kuesioner, and analysed with logistics regression ordinal, with meaning storey level ÃŽÂ± =0,05.Result research show husband support most is goodness (55,0%), most pregnant mother experience to worry lightly (40,0%). From result regresi logistics ordinal got by value p=0,030 matter this means there is influence husband support to anxiety mother during a period pregnancy.Conclusion this research that there is influence husband support to anxiety mother during a period pregnancy. For that health energy expected by counselling about is important inspection pregnancy so that can detect early the existence and also disparity complication which possible happened during pregnancy process and birth.